Trends and influences in social networks and enterprise management research: a bibliometric analysis - Zhang, Yaoyuan; Jamaluddin, Askiah; Lau Leby, Nur Jasmine (Human Resources Management Academic Research Society (HRMARS), 2024)
Social networks have emerged as a critical factor in shaping the landscape of enterprise management, influencing both theoretical development and practical applications. Recognizing their growing importance, this research conducts a bibliometric analysis to map and understand the dynamic trends and influential elements within the intersection of social networks and enterprise management research. The analysis spans a comprehensive period, using data from major academic databases to identify key research themes, prolific authors, and leading organizations contributing to this domain. The study employs the bibliometric approach, incorporating citation analysis, co-authorship networks, and keyword cooccurrence to reveal patterns and relationship within the literature. The results indicate several major trends, including the increasing focus on innovation management and knowledge sharing as critical themes within the enterprise management context. Furthermore, the study identifies a core group od influential authors who have substantially contributed to the foundational theories and methodologies in this filed. The findings suggest that research on social networks in enterprise management is rapidly evolving, with emerging areas. The study concludes by proposing further investigation into underexplored areas, such as cross-cultural influences on social networks in different organizational contexts. This analysis enriches the ongoing academic discourse by providing a detailed overview of the current research landscape, offering critical insights for both academic and practitioners, and setting the stage of future inquiries in this vital area of study.